Treatment Leptospira Infection In Dog At Pet Vet Clinic, Center of Jakarta - Anugrah, Dian; Apada, Andi Magfira Satya; Rell, Fedri; Suharto, Rian Hari; Mursalim, Muhammad Fadhlullah (Universitas Airlangga, 2023)
Leptospirosis is a disease caused by Leptospira spp., zoonotic Gram-negative bacteria. This study aimed to determine the handling of a leptospirosis case in a dog at the Pet Vet Clinic, Jakarta. Handling began with anamnesis and continued by examining the patient's physical condition, followed by serological, microscopic, and polymerase chain reaction examinations. An examination revealed that the dog had Leptospirosis. The therapy given was the administration of crystalline procaine and penicillin-G antibiotics. Supportive treatment was given with hepatoprotective, lipotropic, and diuretic supplements. Ringer's lactate was used as fluid therapy. The treatment administered showed positive, progressive results in the patient.